2010
DOI: 10.1186/1471-2229-10-213
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a natural chloroplast-encoded antisense RNA in tobacco destabilizes 5S rRNA and retards plant growth

Abstract: BackgroundThe roles of non-coding RNAs in regulating gene expression have been extensively studied in both prokaryotes and eukaryotes, however few reports exist as to their roles in organellar gene regulation. Evidence for accumulation of natural antisense RNAs (asRNAs) in chloroplasts comes from the expressed sequence tag database and cDNA libraries, while functional data have been largely obtained from artificial asRNAs. In this study, we used Nicotiana tabacum to investigate the effect on sense strand trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 66 publications
0
35
0
Order By: Relevance
“…We also note that the in vitro experiments used molar ratios of precursor and asRNA that may not represent the ratios of the bioactive molecules in vivo. On the other hand, our recent demonstration that overexpression of AS5 in tobacco chloroplasts destabilizes the 5S rRNA (Hotto et al 2010) supports the viewpoint that the in vitro system is a useful platform for dissecting the mechanism of AS5 action.…”
Section: In Vitro Dissection Of As5 Inhibitor Sequencesmentioning
confidence: 88%
“…We also note that the in vitro experiments used molar ratios of precursor and asRNA that may not represent the ratios of the bioactive molecules in vivo. On the other hand, our recent demonstration that overexpression of AS5 in tobacco chloroplasts destabilizes the 5S rRNA (Hotto et al 2010) supports the viewpoint that the in vitro system is a useful platform for dissecting the mechanism of AS5 action.…”
Section: In Vitro Dissection Of As5 Inhibitor Sequencesmentioning
confidence: 88%
“…Some functional RNAs are defined by 59-end RNA-binding proteins that stall 59 / 39 exonucleolytic activity (Drager et al 1998;Nickelsen et al 1999;Loiselay et al 2008;Johnson et al 2010;Prikryl et al 2010), but other protective mechanisms may also exist. Examples of RNAs probably not protected by PPR-type proteins include natural (i.e., accumulating in the WT) asRNAs (Georg et al 2010;Hotto et al 2010;Sharwood et al 2011), small RNAs involved in splicing or other functions (Goldschmidt-Clermont et al 1991;Vera and Sugiura 1994), as well as rRNAs, tRNAs, and any mRNAs that do not bind protective 59-end proteins. Some of these species may escape RNase J degradation by virtue of associating with proteins, such as ribosomal proteins, splicing factors, or translation factors.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that several recent reports, including our own, had described the accumulation of chloroplast antisense or non-coding RNAs (Lung et al 2006;Georg et al 2010;Hotto et al 2010), and that these might be substrates for RNase J. If this were the case, they could overaccumulate in mutant material.…”
Section: Diffuse Transcripts and Novel Bands Are Mainly Antisense Rnasmentioning
confidence: 99%
“…They focus on single RNAs and do not point to ncRNAs as a more general regulatory principle (Nishimura et al, 2004;Georg et al, 2010;Hotto et al, 2010;Zghidi-Abouzid et al, 2011). One study identified 12 ncRNAs in tobacco chloroplasts (Lung et al, 2006).…”
Section: Plastid Ncrnasmentioning
confidence: 99%
“…Cyanobacteria, the chloroplast progenitors, have a plethora of noncoding RNAs at their disposal to regulate gene expression . However, only a few potentially regulatory RNAs have been reported to be transcribed from plastid genes (Nishimura et al, 2004;Georg et al, 2010;Hotto et al, 2010;Zghidi-Abouzid et al, 2011). Therefore, chloroplasts may contain additional hitherto undetected genes for regulatory ncRNAs.…”
Section: Introductionmentioning
confidence: 99%